?ELEMENTAL ANALYSIS OF CALENDULA OFFICINALIS PLANT AND ITS PROBABLE THERAPEUTIC ROLE IN HEALTH (Biological Sciences - PJSIR, 2003)
Elemental analysis of crude ethanolic and aqueous extracts of Calendula officinalis plant and its individual parts i.e. flowers, leaves and roots reveal the presence of major, minor and trace elements in appreciable quantities. Elements detected in crude ethanolic and aqueous extracts of whole Calendula plant are calcium 5319, 2464 ppm, sodium 16990, 14745 ppm, potassium 79782, 71617 ppm, magnesium 6059, 9060 ppm, iron 74.459, 22.94 ppm, copper 8.05, 1.27 ppm, manganese 37.22, 36.96 ppm, zinc 51.50, 34.00 ppm, nickle 5.10, 2.45 ppm, cobalt 1.39, 0.98 ppm and cadmium 0.40, 0.50 ppm. While chromium and lead were found to be present in 1.01 ppm in ethanolic and in traces in aqueous extracts. Highest percentages of iron 125, 28.16 and copper 80.59, 10.19 ppm were found to be present in ethanolic and aqueous extracts of root portion respectively. The highest quantity of nickle 8.46 ppm was found in aqueous extracts of roots while in ethanolic extract it was 7.10 ppm in flowers. Calendula officinalis and its individual parts were found to be rich in calcium, sodium, potassium and magnesium contents which are not only essential but are also required for the haemostatic control of the body.